Lasers for Onychomycosis: Current Status. Issue 2 (March 2017) - Gupta, Aditya K.; Foley, Kelly A.; Versteeg, Sarah G.
Many studies that have been recently published investigate the efficacy of laser treatment for onychomycosis. These studies support the current US Food and Drug Administration (FDA) approval of lasers for the 'temporary increase in clear nail'. Clear nail growth is an important treatment goal for patients; however, many do not realise that laser treatment is not a cure for onychomycosis. The current article briefly reviews why lasers may be theoretically effective in treating onychomycosis and critically reviews published laser studies for onychomycosis in light of the standards employed in drug trials. Treatment regimens, efficacy endpoints, and the unit of analysis (nails vs patients) vary widely among published laser studies. Complete cure, mycological cure, and clinical improvement rates in laser studies are not reported or use such disparate criteria that comparison among studies is not possible. The US FDA has recently published guidelines for the use of medical devices in clinical trial design for onychomycosis. Future laser studies should adopt the FDA's guidelines to allow for more consistency within the field and focus on the efficacy of lasers as monotherapy for onychomycosis.